ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI PERIODE 2013-2017 - Munawati Caniago; Purwantoro (Program Studi Manajemen Universitas Pasir Pengaraian, 2019)
Earnings management is a manager's actions to choose accounting policies or actions that affect earnings in order to achieve certain objectives in reporting earnings. This study aims to determine the effect of leverage, company size and profitability on earnings management in the textile and garment sub-sector registered in the 2013-2017 period. The population used in this study were all textile and garment sub-sector companies registered in the 2013-2017 period. This study uses a purposive sampling technique with predetermined criteria. The number of samples used were 5 companies. The analysis technique used is multiple linear regression analysis. The results showed that the variable leverage, company size and profitability did not have a significant effect on earnings management either partially or simultaneously.